Perencanaan Bisnis Strategis untuk Sistem Informasi untuk Meningkatkan Layanan Kesehatan Masyarakat - Ambarwati, Rita; Widyasari, Dwi Fitri (Jurnal Teknik Informatika dan Sistem Informasi, 2024)
The system management strategy plays a vital role in maintaining profitability to achieve revenue with a strategic plan that starts in all sectors of life to replace conventional technology-based services. This study aims to improve public health services through hospital environmental conditions so that performance increases and provides added value to increase the hospital's competitive advantage. There are several systems that need to be optimized, so it is necessary to group data with the ease of application systems. The study uses a descriptive descriptive approach with IS business strategy methods, internal and external environmental analysis, SWOT analysis, and McFarlan Strategic Grid analysis on IS applications. From the results of the research that has been done, IS planning is influential in helping management make decisions about a policy in a hospital that is useful for evaluating IS applications that continue to change for the better in the future.